Recognition of a new species of Carmenta from New Mexico supported by morphology and mitochondrial cytochrome oxidase I data (Lepidoptera: Sesiidae: Sesiinae: Synanthedonini) - Taft, William H.; Cognato, Anthony I. (Zootaxa, 2017)
A preliminary phylogeny of 36 species of Carmenta (Lepidoptera: Sesiidae) was reconstructed based on mitochondrial cytochrome oxidase I DNA sequences using parsimony and Bayesian inference in order to assess the placement of a suspected new species. Although the phylogeny was not completely resolved, there were well-supported species groups associated with geography. Based on these results and diagnostic morphological characters, Carmenta wildishorum, n. sp., is described and illustrated from the Cimarron Mountain Range in northeastern New Mexico. The new species is sister to C. texana with a 5.2% nucleotide difference between the two, which is similar to the distance between other Carmenta species and exceeds the intraspecific difference observed within C. texana (0.3%). The phylogeny also suggests additional hidden species diversity among Carmenta species that have large geographic distributions.